2006
DOI: 10.1590/s0044-59672006000400009
|View full text |Cite
|
Sign up to set email alerts
|

Physiographic and floristic gradients across topography in transitional seasonally dry evergreen forests of southeast Pará, Brazil

Abstract: Seasonally dry evergreen forests in southeast Pará, Brazil are transitional between taller closed forests of the interior Amazon Basin and woodland savannas (cerrados) of Brazil's south-central plains. We describe abiotic and biotic gradients in this region near the frontier town of Redenção where forest structure and composition grade subtly across barely undulating topography. Annual precipitation averaged 1859 mm between 1995-2001, with nearly zero rainfall during the dry season months of June -August. Annu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…This region is characterized by semi-evergreen transitional forests grading subtly or abruptly into scrub woodlands (cerradão) or woodland savannas (cerrado) on nutrient-poor, freely draining soils that exacerbate dry season stress on plants. These forests have relatively low and highly irregular canopies subject to frequent small-scale disturbances such as seasonal drought, flooding, and convectional windstorms (Grogan and Galvão, 2006b). These are ideal conditions for mahogany's regeneration and recruitment to adult size in treefall gaps and may help explain relatively high densities observed in this region (Grogan, 2001;Brown et al, 2003).…”
Section: Density Patterns and Size Class Frequency Distributionsmentioning
confidence: 99%
“…This region is characterized by semi-evergreen transitional forests grading subtly or abruptly into scrub woodlands (cerradão) or woodland savannas (cerrado) on nutrient-poor, freely draining soils that exacerbate dry season stress on plants. These forests have relatively low and highly irregular canopies subject to frequent small-scale disturbances such as seasonal drought, flooding, and convectional windstorms (Grogan and Galvão, 2006b). These are ideal conditions for mahogany's regeneration and recruitment to adult size in treefall gaps and may help explain relatively high densities observed in this region (Grogan, 2001;Brown et al, 2003).…”
Section: Density Patterns and Size Class Frequency Distributionsmentioning
confidence: 99%
“…While all sites receive <2200 mm of rainfall annually and are seasonally dry during 1-6 months of the year, underlying geomorphology and soil physical and chemical properties vary widely among sites (IBGE, 2003;Schulze, 2003;Grogan and Galvão, 2006). As a consequence, forest structure ranges from tall closed evergreen canopies in eastern forests (sites A-C) to tall open evergreen forests in the southwest (F and G), low broken semi-evergreen forest in the southeast (D), and open semideciduous forest in Rondô nia (E).…”
Section: Inventoriesmentioning
confidence: 99%
“…Within the study area, Swietenia macrophylla is nearly always found at highest densities along the banks of small seasonally dry streams and in adjacent lowlying, flat areas with poorly drained soils, sharing this habitat with the palm species Orbignya phalerata Mart. and Maximiliana maripa (Aublet) Drude (Grogan and Galvão 2006). It is usually not found in the denser and taller upper slope or middle slope forest communities.…”
Section: Study Sitementioning
confidence: 99%
“…The clumped distribution of S. macrophylla trees at Marajoara reflects the adaptation by the species to colonise gaps created by canopy disturbances occurring at a higher frequency on low ground compared to high ground, coupled with more nutrient-rich soils along seasonal streams (Grogan et al 2003;Grogan and Galvão 2006). Swietenia macrophylla populations established in new areas are likely to have experienced demographic bottlenecks due to the putative small number of founders following successful establishment.…”
Section: Genetic Diversity In Adults and Seedsmentioning
confidence: 99%